[Math] Formal Proof – Propositional Logic

logic

I missed this class on formal proofs and apparently the professor is not going over it any longer. I'm stuck on this current question in the textbook and I'm unsure on what the procedures are to solve a question of this sort. I have provided the slide where the rules are given but I have no clue how to implement these rules into this question. Not even sure how the steps to giving a formal proof even look like as the slides provided to me are not very descriptive. I would truly appreciate some help here. Thanks

Question

Rules

Best Answer

For a) :

1) $(A \lor B) \land \lnot C$ --- premise

2) $\lnot C \to (D \land \lnot A)$ --- premise

3) $B \to (A \lor E)$ --- premise

4) $A \lor B$ --- from 1) by $\land$-elimination

5) $\lnot C$ --- from 1) by $\land$-elimination

6) $D \land \lnot A$ --- from 2) and 5) by $\to$-elimination

7) $\lnot A$ --- from 6) by $\land$-elimination

8) $A$ --- assumed [a]

9) $A \lor E$ --- from 8) by $\lor$-introduction

10) $B$ --- assumed [b]

11) $A \lor E$ --- from 10) and 3) by $\to$-elimination

12) $A \lor E$ --- from 4), 8)-9) and 10)-11) by $\lor$-elimination, discharging temporary assumptions [a] and [b]

13) $\lnot E$ --- assumed [c]

14) $A$ --- assumed [d]

15) $\bot$ --- contradiction : from 7) and 14) by $\bot$-introduction

16) $E$ --- assumed [e]

17) $\bot$ --- contradiction : from 13) and 16) by $\bot$-introduction

18) $\bot$ --- from 12), 13)-14) and 15)-16) by $\lor$-elimination, discharging temporary assumptions [d] and [e]

19) $E$ --- from 13) and 18) by RAA, discharging temporary assumption [c]

20) $E \lor F$ --- from 19) by $\lor$-introduction.


Note

In order to complete the proof, we need the rules for $\bot$ (as in the link referred into the above comment) :

$\bot \vdash A$ (RAA or $\bot$-elimination)

and :

$A, \lnot A \vdash \bot$ ($\lnot$-elimination).



For b) :

1) $(A \to F) \land (F \to D)$ --- premise

2) $((M \lor H) \lor C) \to A$ --- premise

3) $\lnot (M \lor H) \land C$ --- premise

4) $A \to F$ --- from 1) by $\land$-elimination

5) $F \to D$ --- from 1) by $\land$-elimination

6) $C$ --- from 3) by $\land$-elimination

7) $(M \lor H) \lor C$ --- from 6) by $\lor$-introduction

8) $A$ --- from 7) and 2) by $\rightarrow$-elimination

9) $F$ --- from 8) and 4) by $\rightarrow$-elimination

10) $D$ --- from 9) and 5) by $\rightarrow$-elimination.

Related Question